Carbon ion radiotherapy in pancreatic cancer: a review of clinical data - Liermann, Jakob; Shinoto, Makoto; Syed, Mustafa; Debus, Jürgen; Herfarth, Klaus; Naumann, Patrick (Radiotherapy and oncology, 2020)
Despite all efforts, pancreatic cancer remains a highly lethal disease. Only surgical resection offers a realistic chance of survival. But at diagnosis the majority of patients suffer from unresectable disease. Whereas guidelines clearly recommend systemic treatments in metastatic disease, data is limited to support a specific treatment option for locally advanced or borderline resectable pancreatic cancer. Therefore, there is an urgent need to improve treatment schemes addressing patients that suffer from unresectable pancreatic cancer. Chemotherapy, photon radiotherapy and combinations of both have shown improved local control rates but there is still a lack of evidence demonstrating an overall survival benefit of photon radiotherapy if no surgical resection is achieved. Impressive results of Japanese Phase I/II-trials investigating carbon ion radiotherapy in pancreatic cancer attracted global attention. Several studies have been initiated to validate and intensify this promising issue. This review gives an overview of the evidence and current use of carbon ion radiotherapy in pancreatic cancer.